EFFECTIVENESS OF CRIMINAL CRIMINAL INVESTIGATIONS IN HOUSEHOLD IN PALOPO POLICE LAW AREA - Andi Ahmad Akbar; Hambali Thalib; Sufirman Rahman (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal